Sammy Claws the Christmas cat - Rowland, Lucy (Nosy Crow, 2018)
Sammy Claws, Santa's cuddly pet cat, will sleep anywhere and as he sleeps he dreams ... Sammy longs to fly with Santa on his sleigh, but when he accidentally causes mayhem in the workshop, it looks like he has lost his chance. That is until, snoozing in a box, Sammy finds himself wrapped up as a Christmas parcel and bundled onto the sleigh with the other presents. How will Sammy escape? And how will he save the presents from two rotten robbers with plans to steal them all away . . .?